High-entropy alloy nanowire, preparation method thereof and composite catalyst

Through the use of platinum sources, sources, and non -precious metal salts during the preparation of high -entropy alloy nano nanosaic wiring, and combined with magnetic field regulation, the problem of serious pollution and high energy consumption of existing technology in the existing technology has been solved. Preparation of high entropy alloy nano wires has excellent catalytic performance and stability.

CN119368755AActive Publication Date: 2025-01-28GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411518674.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-28
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The preparation method of high-entropy alloy nanowires in the prior art has problems of serious pollution and high energy consumption, making it difficult to achieve large-scale and commercial production.

Method used

The reaction raw material for the reaction raw material for the complacent source, the source of the pupae, and the non -precious metal salt as the high -entropy alloy nano line, and add the magnetic field during the reduction process to prepare the diameter of the diameter and growth process of the magnetic metal particles by magnetic the magnetic metal particles through the magnetic metal particles. High -entropy alloy nano wires with long length, consistent growth direction, pure, and high decentralization.

Benefits of technology

The low -cost and low energy consumption preparation of high -entropy alloy nano lines has high catalytic activity and stability, suitable for large -scale production, and showing excellent catalytic performance in the oxygen reduction reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368755A_ABST
    Figure CN119368755A_ABST
Patent Text Reader

Abstract

The preparation method comprises the steps that a metal precursor mixed solution containing a nucleating agent, a complexing agent, ammonium salt, non-noble metal salt and a solvent is placed in an exogenous magnetic field, a reducing agent is added for a reduction reaction, and the high-entropy alloy nanowire is obtained; the nucleating agent comprises a platinum source and a palladium source; the non-noble metal salt comprises a combination of at least three of ferric salt, cobalt salt, nickel salt, copper salt or manganese salt. A platinum source, a palladium source and non-noble metal salt are used as reaction raw materials of the high-entropy alloy nanowire, a magnetic field is added, and in the reduction process, the nucleation and growth process of magnetic metal particles and the self-assembly behavior of magnetic nanocrystals are regulated and controlled through magnetic force, so that the high-entropy alloy nanowire is obtained. The high-entropy alloy nanowire which is adjustable in length-diameter ratio, stable in structure and uniform in Pt dispersion can be prepared under the conditions of room temperature and normal pressure, and the composite catalyst obtained after the high-entropy alloy nanowire is mixed with commercial carbon powder is rich in active sites and excellent in oxygen reduction catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano materials and catalysts, and in particular to a high entropy alloy nanowire and a preparation method thereof and a composite catalyst. Background Art

[0002] High entropy alloys (HEAs) have rich composition space, multiple active sites, nearly continuously adjustable binding energy and stable structure, which enable them to be widely used in the field of electrocatalysis and have extremely broad prospects in catalysis and energy applications. Among them, high entropy alloy nanowires (NWs) with a one-dimensional morphology and a high aspect ratio are one of the important branches of high entropy alloy materials. Compared with traditional zero-dimensional high entropy alloy nanoparticles, one-dimensional nanowires have unique structures and surface properties, showing better conductivity and higher bonding strength with the carrier. In addition, the anisotropic structure of the one-dimensional morphology is more resistant to Ostwald ripening, which makes the high entropy alloy nanowires have better stability and better catalytic effect when used in catalysts.

[0003] A fuel cell is a power generation device that converts chemical energy into electrical energy. It has the advantages of high energy conversion efficiency, mild reaction conditions, and a wide range of fuel selection. The electrodes of a fuel cell are the electrochemical reaction sites where the fuel undergoes oxidation reaction and the oxidant undergoes reduction reaction. The catalyst loaded on the electrode is the main reason that limits its development. The oxygen reduction (ORR) reaction rate at the cathode is much slower than that at the anode. Therefore, the development of low-cost, highly active, and highly stable ORR catalysts is the current research focus.

[0004] Pt-based high entropy alloy nanowires have excellent ORR activity. Compared with traditional Pt nanoparticle catalysts, the lattice distortion characteristics of high entropy alloy nanowire catalysts promote the formation of defects and strains. The special organizational structure makes it have excellent stability. At the same time, the heterogeneous interface can provide more abundant active sites and moderate adsorption free energy. In addition, compared with zero-dimensional nanoparticles, the special structure of one-dimensional nanowires makes its contact area with the carbon support larger, enhances the interaction with the carbon support, thereby preventing the catalyst from falling off, and thus the stability of the ORR reaction is higher. Nanowires also have better conductivity and have smooth electron transmission channels in the ORR reaction. At the same time, the consistent crystal orientation in the nanowires further regulates the adsorption and desorption of oxygen intermediates, reflecting the high catalytic activity of the ORR reaction.

[0005] At present, the methods for synthesizing high entropy alloy nanowires include: focused ion beam cutting method, organic phase reduction method or aqueous phase thermal reduction method, etc. The prior art discloses a method for preparing ultra-thin nanowires, in which Re is doped into ultra-thin PtNiGa nanowires in trace amounts to prepare Re-PtNiGaNWs catalysts, and the preparation method includes: in an oleylamine organic phase, using hexacarbonyl tungsten as a reducing agent, heating at 170°C for 2h to reduce acetylacetonate, centrifuging and washing with a hexane / ethanol mixture for multiple times and then drying to obtain the product. Although compared with traditional platinum-carbon catalysts, the catalytic activity and stability of the catalyst obtained by this preparation method are improved to a certain extent, but in the process of catalyst preparation, the use of organic phase and detergent causes a lot of air pollution, the carbon monoxide decomposed by hexacarbonyl tungsten is extremely harmful to the human body, and heating at 170°C for 2h requires a lot of energy input. In general, it is difficult to achieve scale-up production, and it is difficult to meet the requirements of commercial applications.

[0006] Studies have shown that magnetic fields can affect the nucleation and growth process of magnetic materials and the self-assembly behavior of magnetic nanocrystals, greatly reducing the difficulty of nanowire growth. This provides ideas for developing a new method for synthesizing high-entropy alloy nanowires.

[0007] The prior art discloses a preparation method for the growth of nanowires assisted by a magnetic field. In this technology, hydrazine hydrate is used as a reducing agent in an aqueous phase under a magnetic field formed by a bar magnet, and a chloride salt is reduced by heating at 90°C for a period of time to obtain a black intermediate product, which is washed with ethanol and water for multiple times and then dried. The intermediate product is placed in a tubular furnace and heated at 300°C for 3 hours under a hydrogen (H2) atmosphere with a flow rate of 200 mL / min to obtain FeCo nanowires. Although this preparation method synthesizes nanowires under a magnetic field, which reduces the difficulty of chemical reduction, the means of controlling the magnetic field using a bar magnet is single, and the species to be reduced (only Fe and Co) are relatively few. Heating at 300°C for 3 hours requires a large amount of energy input, which is not conducive to industrialization and is still far from large-scale production.

[0008] Since the above preparation methods all have the problems of serious pollution and high energy consumption, and thus cannot realize large-scale and commercial production of high-entropy alloy nanowires, how to develop a synthesis method of high-entropy alloy nanowires to reduce pollution and energy consumption and realize large-scale production, and at the same time, the obtained high-entropy alloy nanowires can be used as ORR catalysts with certain catalytic activity and stability, is a technical problem that needs to be solved urgently. Summary of the invention

[0009] In order to solve the above technical problems, the present invention provides a high entropy alloy nanowire, a preparation method thereof and a composite catalyst. Platinum source, palladium source and non-precious metal salt are used as reaction raw materials of the high entropy alloy nanowire, and a magnetic field is added. During the reduction process, the nucleation and growth process of magnetic metal particles and the self-assembly behavior of magnetic nanocrystals are regulated by magnetic force, so that high entropy alloy nanowires with adjustable diameter and length, consistent growth direction, purity, high dispersion, stable structure and uniform Pt dispersion can be prepared at room temperature and normal pressure. The composite catalyst obtained after mixing with commercial carbon powder has rich active sites and excellent oxygen reduction catalytic activity. The preparation method of the present invention can be carried out at room temperature and normal pressure, and has the advantages of low synthesis temperature, lower cost, less harm, simpler equipment, higher yield and more uniform nanowires.

[0010] To achieve this object, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a method for preparing high entropy alloy nanowires, the preparation method comprising the following steps:

[0012] placing the metal precursor mixed solution under an external magnetic field, adding a reducing agent to carry out a reduction reaction, and obtaining high entropy alloy nanowires;

[0013] Wherein, the metal precursor mixed solution comprises a nucleating agent, a complexing agent, an ammonium salt, a non-precious metal salt and a solvent;

[0014] The nucleating agent includes a platinum source and a palladium source;

[0015] The non-noble metal salt includes a combination of at least three of an iron salt, a cobalt salt, a nickel salt, a copper salt or a manganese salt.

[0016] The present invention uses a platinum source, a palladium source, a non-precious metal salt, an ammonium salt and a complexing agent to work together to obtain a high-entropy alloy nanowire with adjustable diameter and length, consistent growth direction, purity, high dispersion, stable structure and uniform Pt dispersion. Platinum source, palladium source and non-precious metal salt are used as reaction raw materials for high-entropy alloy nanowires, wherein the platinum source and palladium source also act as nucleating agents for the reaction. Under the action of the reducing agent, the nucleating agent forms a sufficient number of uniformly distributed crystal nuclei, providing a starting point for the growth of non-precious metal atoms, and overall reduces the barrier for nucleation of metal grains, making the reduction reaction easier to carry out; the metal in the non-precious metal salt used in the present invention may be all or partly magnetic, and the metal grains may be arranged and grown along the direction of the magnetic field to form an ordered nanowire structure, so that the controllable aspect ratio can be prepared at room temperature. , uniformly dispersed and structurally stable high-entropy alloy nanowires; the addition of ammonium salts can, on the one hand, play the role of surfactants, increase the polarity of the reaction raw materials, and promote the dispersion and dissolution of the reaction raw materials in water; on the other hand, ammonium salts can also be used as buffer solutions for pH regulators to a certain extent, thereby avoiding large-scale changes in pH and affecting the formation of nanowire morphology; the addition of chelating agents can form complexes with metal ions, control the reaction to proceed slowly, and allow the metal ions to have enough time to grow in an orderly manner under the action of the magnetic field, thereby avoiding rapid reduction of metal ions that causes them to escape the control of the magnetic field and ultimately obtain metal nanoparticles.

[0017] The preparation method of the high entropy alloy nanowires provided by the present invention is mainly assisted by the addition of a magnetic field. During the reducing agent process, the magnetic force provided by the magnetic field regulates the nucleation and growth of magnetic metal particles along the direction of the magnetic field, as well as the self-assembly behavior of magnetic nanocrystals, so that high entropy alloy nanowires with adjustable diameter and length, consistent growth direction, purity and high dispersion can be prepared at room temperature (10-35°C) and normal pressure.

[0018] As a preferred technical solution of the present invention, in the non-precious metal salt, the molar ratio of iron salt, cobalt salt, nickel salt, copper salt and manganese salt is 1:(0-10):(0-10):(0-5):(0-5), and the molar amount of at least two metal salts is not 0, for example, 1:0.5:0.5:0:0, 1:0.5:1:1:3, 1:0:2:0:1, 1:1:0:2:2, 1:5:0:5:0, 1:3:5:0:0, 1:0:1:2:1, 1:10:10:1:1, 1:10:10:3:4 or 1:10:10:5:5, etc.

[0019] Preferably, the type of salt in the non-precious metal salt includes any one of chloride, nitrate, acetate, sulfate, acetylacetonate or phthalocyanine salt, or a combination of at least two thereof.

[0020] Preferably, the platinum source includes any one of chloroplatinic acid, potassium chloroplatinate or sodium chloroplatinate, or a combination of at least two of them.

[0021] Preferably, the palladium source includes any one of chloropalladic acid, palladium chloride or potassium chloropalladate, or a combination of at least two thereof.

[0022] It should be noted that the present invention does not make any specific requirements or special limitations on the solvent. As long as it is a type commonly used by those skilled in the art, it is applicable to the present invention, for example, it can be deionized water, ultrapure water or ethanol.

[0023] Preferably, the complexing agent includes any one of sodium citrate, potassium citrate, citric acid, disodium edetate or tartaric acid, or a combination of at least two thereof.

[0024] Preferably, the ammonium salt includes any one of ammonium fluoride or ammonium chloride or a combination of at least two of them.

[0025] As a preferred technical solution of the present invention, in the metal precursor mixed solution, the molar ratio of the nucleating agent, the complexing agent, the ammonium salt and the non-precious metal salt is 1:(10-500):(200-1500):(0.5-10), for example, 1:10:200:0.5, 1:15:500:1, 1:50:1000:5, 1:100:1200:8, 1:300:1500:10 or 1:500:1500:1, etc.

[0026] Preferably, in the metal precursor mixed solution, the concentration of the metal element is 0mmol / L-0.5mmol / L, and is not 0, for example, 0.05mmol / L, 0.1mmol / L, 0.2mmol / L, 0.3mmol / L, 0.4mmol / L or 0.5mmol / L.

[0027] Preferably, the metal precursor mixed solution also includes a pH adjuster.

[0028] It should be noted that the present invention does not make any specific requirements or special limitations on the pH adjuster. As long as it is a type commonly used by technicians in this field, it is applicable to the present invention, for example, it can be sodium hydroxide, potassium hydroxide, hydrochloric acid, sulfuric acid, nitric acid or sodium carbonate.

[0029] As a preferred technical solution of the present invention, the pH of the metal precursor mixed solution is 3-14, for example, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14, etc., preferably 8-13.

[0030] Preferably, the method for preparing the metal precursor mixed solution comprises: dissolving a nucleating agent, a complexing agent, an ammonium salt and a non-precious metal salt in a solvent, mixing them evenly, and adding a pH regulator to obtain the metal precursor mixed solution.

[0031] As a preferred technical solution of the present invention, the field strength of the external magnetic field is 0.0001T-10T, for example, 0.0001T, 0.0005T, 0.01T, 0.05T, 0.08T, 0.1T, 0.5T, 1T, 3T, 5T, 8T or 10T.

[0032] The field strength of the external magnetic field of the present invention is 0.0001T-10T, which can make the non-precious metal ions grow in a directional and orderly manner under the magnetic field to obtain high-entropy alloy nanowires; if the strength is too high, the non-precious metal ions adhere to the reactor wall, making it difficult to grow with precious metal nucleation as the starting point, and high-entropy alloy nanowires with a large aspect ratio cannot be obtained; if the strength is too low, the magnetic field is difficult to guide the directional arrangement of non-precious metals, and ultimately a disordered and chaotic network structure is generated.

[0033] It should be noted that the present invention does not make any specific requirements or special limitations on the device for generating the external magnetic field. As long as it is a type commonly used by technicians in this field, it is applicable to the present invention, for example, it can be a bar magnet, a ring magnet or an electromagnet.

[0034] It should be noted that the present invention does not make any specific requirements or special limitations on the type of the external magnetic field. As long as it is a type commonly used by technicians in this field, it is applicable to the present invention, for example, it can be a constant magnetic field, an alternating magnetic field or a pulsed magnetic field.

[0035] As a preferred technical solution of the present invention, the reducing agent includes sodium borohydride.

[0036] Preferably, the molar ratio of the reducing agent to the metal element is (2-100):1, for example, 2:1, 5:1, 8:1, 50:1, 80:1 or 100:1, etc.

[0037] Preferably, the reduction reaction is carried out at room temperature.

[0038] It should be noted that the reaction described in the present invention is carried out at room temperature, that is, the reaction does not need to be heated. Depending on the region and season, the temperature of the reduction reaction is 10-35°C, for example, 10°C, 12°C, 15°C, 18°C, 20°C, 22°C, 25°C, 28°C, 30°C, 32°C or 35°C, etc., to obtain high-entropy alloy nanowires with high aspect ratio and uniform morphology, avoiding reactions at heating temperatures and simplifying the experimental process.

[0039] Preferably, the reduction reaction time is 0.01-24 h, for example 0.01 h, 0.05 h, 0.1 h, 0.5 h, 0.8 h, 1 h, 5 h, 8 h, 10 h, 12 h, 15 h, 18 h, 20 h, 22 h or 24 h, etc.

[0040] As a preferred technical solution of the present invention, after the reduction reaction, solid-liquid separation, washing and drying are also included.

[0041] Preferably, the solid-liquid separation method includes separation using magnets.

[0042] In the present invention, the product and the solution can be quickly separated by magnetic separation, and the separation method is simple and efficient.

[0043] Preferably, the washing liquid for washing comprises any one of deionized water, ultrapure water, ethanol or cyclohexane, or a combination of at least two thereof.

[0044] Preferably, the drying comprises any one of air drying, vacuum drying or freeze drying, or a combination of at least two thereof.

[0045] Preferably, the drying comprises a combination of freeze drying and vacuum drying, or a combination of freeze drying and forced air drying.

[0046] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0047] The nucleating agent, the complexing agent, the ammonium salt and the non-precious metal salt are dissolved in a solvent and mixed evenly, a pH adjusting agent is added to obtain a metal precursor mixed solution with a pH of 8-13, the mixed solution is placed under an external magnetic field with a field strength of 0.0001-10T, a reducing agent is added to carry out a reduction reaction, and after reduction for 0.01-24h at room temperature, the reaction product is separated by a magnet, and after washing and drying, a high entropy alloy nanowire is obtained;

[0048] Wherein, the nucleating agent includes a platinum source and a palladium source; the non-precious metal salt includes a combination of at least three of iron salt, cobalt salt, nickel salt, copper salt or manganese salt; in the non-precious metal salt, the molar ratio of iron salt, cobalt salt, nickel salt, copper salt and manganese salt is 1:(0-10):(0-10):(0-5):(0-5), and the molar amount of at least two metal salts is not 0; in the metal precursor mixed solution, the molar ratio of nucleating agent, complexing agent, ammonium salt and non-precious metal salt is 1:(10-500):(200-1500):(0.5-10); in the metal precursor mixed solution, the concentration of metal element is 0mmol / L-0.5mmol / L, and is not 0; the reducing agent includes sodium borohydride; the molar ratio of the reducing agent to the metal element is (2-100):1.

[0049] In the second aspect, the present invention also provides a high entropy alloy nanowire prepared by the preparation method according to the first aspect, wherein the diameter of the high entropy alloy nanowire is 100nm-300nm, for example, 100nm, 150nm, 200nm, 250nm or 300nm, etc.; the length is 5μm-80μm, for example, 5μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm or 80μm, etc.

[0050] In a third aspect, the present invention further provides a composite catalyst, which comprises a high entropy alloy nanowire prepared by the preparation method as described in the first aspect, or a high entropy alloy nanowire as described in the second aspect.

[0051] In the present invention, since the nucleating agent includes a platinum source, a certain amount of Pt is dispersed in the composite catalyst, providing active sites for oxygen reduction catalysis. At the same time, the structure of the Pt-based high-entropy alloy nanowires has a large number of heterogeneous interfaces, providing more abundant active sites and appropriate adsorption free energy. The nanowire structure has more excellent conductivity and has a smooth electron transmission channel in the ORR reaction, which overall reflects the high catalytic activity of the ORR reaction.

[0052] Compared with the prior art, the present invention has at least the following beneficial effects:

[0053] 1) The present invention uses the synergistic effect between the raw materials and the content relationship between them, combined with pH regulation, the addition of an external magnetic field and the reduction of a reducing agent, to prepare high entropy alloy nanowires at room temperature with better morphology, higher aspect ratio and no branches.

[0054] 2) The high entropy alloy nanowires prepared by the present invention have a stable structure and uniform Pt dispersion. The composite catalyst obtained after mixing with commercial carbon powder has a large amount of high entropy alloy crystal structure and nanowire morphology orientation, rich active sites, and excellent oxygen reduction catalytic activity. The initial mass activity at 0.9V is 135mA / mg or above, and can reach up to 336mA / mg.

[0055] 3) The preparation method of the present invention is simple and universal, and the reaction process can be carried out at room temperature and normal pressure, which is safe and pollution-free and suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 This is a SEM image of the high entropy alloy nanowires prepared in Example 1 of the present invention.

[0057] Figure 2 This is the EDS image of the high entropy alloy nanowires prepared in Example 1 of the present invention.

[0058] Figure 3This is a SEM image of the high entropy alloy prepared in Comparative Example 1 of the present invention.

[0059] Figure 4 3 is a SEM image of the alloy prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0060] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0061] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0062] The commercial Pt / C catalyst used in Comparative Application Example 4 of the present invention has a Pt loading of 20 wt % and is purchased from Shanghai Sanshe Industrial Co., Ltd.

[0063] Example 1

[0064] This embodiment provides a method for preparing high entropy alloy nanowires, the preparation method comprising the following steps:

[0065] Weigh 0.05mmol H2PtCl6, 0.01mmol PdCl2, 1mmol sodium citrate, 50mmol ammonium fluoride, 0.04mmol FeSO4, 0.01mmol CoSO4 and 0.01mmol NiSO4 in a reaction container, wherein the molar ratio of nucleating agent (H2PtCl6 and PdCl2): sodium citrate: ammonium fluoride: non-precious metal salt is 1:16.7:833.3:1, and the molar ratio of FeSO4:CoSO4:NiSO4 is 1:0.25:0.25), add 400mL deionized water, stir evenly, then add solid sodium hydroxide, continue stirring until the pH is adjusted to 12, and obtain a metal element concentration of 0.3mmol / L of a metal precursor mixed solution, the obtained metal precursor mixed solution was transferred to a 0.2T constant magnetic field generated by an electromagnet, 1mmol of sodium borohydride (the molar ratio of sodium borohydride to metal element is 8.33:1) was added, and the reaction was allowed to stand for 12h; the reaction product was separated by a magnet, washed three times with deionized water and then three times with ethanol, then dispersed in tert-butanol, and freeze-dried using a freeze dryer to obtain high entropy alloy nanowires PtPdFeCoNi-NWs.

[0066] Figure 1 The SEM image of the high entropy alloy nanowires prepared in this embodiment is shown. It can be seen from the image that the high entropy alloy nanowires have uniform morphology, are relatively dispersed, have no branches, and have consistent growth orientation.

[0067] Figure 2 The EDS image of the high entropy alloy nanowires prepared in this embodiment is shown. As can be seen from the image, the Pt content is relatively high, and it can be used as a catalyst.

[0068] Example 2

[0069] This embodiment provides a method for preparing high entropy alloy nanowires, the preparation method comprising the following steps:

[0070] Weigh 0.05mmol H2PtCl6, 0.01mmol PdCl2, 0.6mmol sodium citrate, 15mmol ammonium fluoride, 0.015mmol FeSO4, 0.0075mmol CoSO4 and 0.0075mmol NiSO4 is placed in a reaction container, wherein the molar ratio of nucleating agent (H2PtCl6 and PdCl2): sodium citrate: ammonium fluoride: non-precious metal salt is 1:10:250:0.5, and the molar ratio of FeSO4:CoSO4:NiSO4 is 1:0.5:0.5), 180 mL of deionized water is added thereto, and the mixture is stirred evenly. Solid sodium hydroxide is then added thereto, and stirring is continued until the pH is adjusted to 10 to obtain a metal precursor mixed solution with a metal element concentration of 0.5 mmol / L. The obtained metal precursor mixed solution is transferred to a 5 T constant magnetic field generated by an electromagnet, 1.8 mmol of sodium borohydride (the molar ratio of sodium borohydride to the metal element is 20:1) is added, and the reaction is allowed to stand for 18 hours; the reaction product is separated with a magnet, washed three times with deionized water and then three times with ethanol, and then dispersed in tert-butanol, and freeze-dried using a freeze dryer to obtain high entropy alloy nanowires PtPdFeCoNi-NWs.

[0071] Example 3

[0072] This embodiment provides a method for preparing high entropy alloy nanowires, the preparation method comprising the following steps:

[0073] Weigh 0.05mmol H2PtCl6, 0.01mmol PdCl2, 30mmol sodium citrate, 60mmol ammonium fluoride, 0.06mmol FeSO4, 0.024mmol CoSO4, 0.024mmol NiSO4 and 0.012mmol MnSO4 in a reaction container, wherein the molar ratio of nucleating agent (H2PtCl6 and PdCl2): sodium citrate: ammonium fluoride: non-precious metal salt is 1:500:1000:2, and the molar ratio of FeSO4:CoSO4:NiSO4:MnSO4 is 1:0.4:0.4:0.2). Add 450mL of deionized water, stir evenly, then add solid sodium hydroxide, and continue stirring until the pH is adjusted to 9 to obtain a metal element concentration of 0.4m mol / L of a metal precursor mixed solution, the obtained metal precursor mixed solution was transferred to a 10T constant magnetic field generated by an electromagnet, 0.36mmol of sodium borohydride (the molar ratio of sodium borohydride to metal element is 2:1) was added, and the reaction was allowed to stand for 0.5h; the reaction product was separated by a magnet, washed three times with deionized water and then three times with ethanol, and then dispersed in tert-butanol, and freeze-dried using a freeze dryer to obtain high entropy alloy nanowires PtPdFeCoNi-NWs.

[0074] Example 4

[0075] This embodiment provides a method for preparing high entropy alloy nanowires, the preparation method comprising the following steps:

[0076] Weigh 0.05mmol H2PtCl6, 0.01mmol PdCl2, 18mmol sodium citrate, 90mmol ammonium fluoride, 0.12mmol FeSO4, 0.30mmol CoSO4 and 0.18mmol CuSO4 is placed in a reaction container, wherein the molar ratio of nucleating agent (H2PtCl6 and PdCl2): sodium citrate: ammonium fluoride: non-precious metal salt is 1:300:1500:10, and the molar ratio of FeSO4:CoSO4:CuSO4 is 1:2.5:1.5), 1320 mL of deionized water is added thereto, and the mixture is stirred evenly. Solid sodium hydroxide is then added thereto, and stirring is continued until the pH is adjusted to 13 to obtain a metal precursor mixed solution with a metal element concentration of 0.5 mmol / L. The obtained metal precursor mixed solution is transferred to a 0.2 T constant magnetic field generated by an electromagnet, 66 mmol of sodium borohydride (the molar ratio of sodium borohydride to the metal element is 100:1) is added, and the reaction is allowed to stand for 24 hours; the reaction product is separated with a magnet, washed three times with deionized water and then three times with ethanol, and then dispersed in tert-butanol, and freeze-dried using a freeze dryer to obtain high entropy alloy nanowires PtPdFeCoNi-NWs.

[0077] Example 5

[0078] This embodiment provides a method for preparing high entropy alloy nanowires. The difference between the preparation method and Example 1 is that the molar ratio of nucleating agent: sodium citrate: ammonium fluoride: non-precious metal salt is 1:16.7:833.3:0.25, and the other preparation methods and parameters are consistent with Example 1.

[0079] Example 6

[0080] This embodiment provides a method for preparing high entropy alloy nanowires. The difference between the preparation method and Example 1 is that the molar ratio of nucleating agent: sodium citrate: ammonium fluoride: non-precious metal salt is 1:16.7:833.3:12, and the other preparation methods and parameters are consistent with Example 1.

[0081] Example 7

[0082] This embodiment provides a method for preparing high entropy alloy nanowires. The difference between the preparation method and Example 1 is that the constant magnetic field generated by the electromagnet is 13 T, and the other preparation methods and parameters are consistent with Example 1.

[0083] Example 8

[0084] This embodiment provides a method for preparing high entropy alloy nanowires. The difference between the preparation method and Example 1 is that, during the reduction process, 13.2 mmol of sodium borohydride (the molar ratio of sodium borohydride to the metal element is 110:1) is added, and the rest of the preparation method and parameters are consistent with Example 1.

[0085] Example 9

[0086] This embodiment provides a method for preparing high entropy alloy nanowires. The difference between the preparation method and Example 1 is that, during the reduction process, 0.12 mmol of sodium borohydride (the molar ratio of sodium borohydride to the metal element is 1:1) is added, and the remaining preparation methods and parameters are consistent with Example 1.

[0087] Comparative Example 1

[0088] This comparative example provides a method for preparing a high entropy alloy. The difference between the preparation method and Example 1 is that the assistance of the external magnetic field is omitted, and the rest of the preparation method and parameters are consistent with Example 1.

[0089] Figure 3 The SEM image of the high entropy alloy prepared in this comparative example is shown. It can be seen from the image that the high entropy alloy has a non-nanowire morphology, and is an agglomerated aerogel structure.

[0090] Comparative Example 2

[0091] This comparative example provides a method for preparing an alloy. The difference between the preparation method and Example 1 is that the addition of nucleating agents H2PtCl6 and PdCl2 is omitted, and the rest of the preparation method and parameters are consistent with Example 1.

[0092] Since the addition of nucleating agents H2PtCl6 and PdCl2 was omitted, no product was generated in the solution after reduction in this comparative example.

[0093] Comparative Example 3

[0094] This comparative example provides a method for preparing an alloy. The difference between the preparation method and Example 1 is that the addition of FeSO4, CoSO4 and NiSO4 is omitted, that is, the addition of non-precious metal salts is omitted, and the rest of the preparation method and parameters are consistent with Example 1.

[0095] Figure 4 The SEM image of the alloy prepared in this comparative example is shown. It can be seen from the image that the alloy has a non-nanowire morphology and is a loose aerogel structure.

[0096] The diameter and length of the high entropy alloy nanowires prepared in Examples 1-9 were measured using a linear distance measurement method using a scanning electron microscope and the average values ​​were taken. The specific test data are shown in Table 1.

[0097] Table 1

[0098] project Average length (μm) Average diameter(nm) Aspect Ratio Example 1 50 200 250:1 Example 2 30 130 231:1 Example 3 18 110 164:1 Example 4 70 280 250:1 Example 5 10 70 143:1 Example 6 70 350 200:1 Example 7 10 1000 10:1 Example 8 15 80 187:1 Example 9 3 100 30:1 Comparative Example 1 / / / Comparative Example 2 / / / Comparative Example 3 / / /

[0099] Note: “ / ” indicates that no nanowire morphology was generated and the average length and average diameter could not be tested.

[0100] The test results show that:

[0101] (1) It can be seen from Examples 1 to 4 that the high entropy alloy nanowires prepared by the preparation method of the present invention all meet the requirements of a diameter of 100 nm to 300 nm, a length of 5 μm to 80 μm, a relatively high aspect ratio, a relatively good morphology, and no branches. When further applied to a composite catalyst, a certain amount of active sites can be exposed to ensure that the catalyst has a certain activity. The preparation method of the present invention is simple and universal, and the reaction process can be carried out at room temperature and normal pressure, which is safe and pollution-free and suitable for mass production.

[0102] Furthermore, when the content of non-precious metal salt is too high or too low, the constant magnetic field is too high or too low, or the content of sodium borohydride is too high or too low, it will affect the morphology and size of the prepared high-entropy alloy nanowires, thereby affecting the dispersion of Pt on the surface of the nanowires, resulting in a reduction in the number of active sites. When further applied to a composite catalyst, the performance of the catalyst will be reduced.

[0103] (2) It can be seen from Comparative Examples 1-3 that if the present invention omits the assistance of the external magnetic field, or omits the addition of the nucleating agents H2PtCl6 and PdCl2, or omits the addition of non-precious metal salts, no high entropy alloy nanowire morphology can be obtained; in Comparative Example 2, due to the omission of the nucleating agent, no product is generated, which further indicates that the nucleating agent shows an overall effect of reducing the barrier to nucleation of metal grains, making the reduction reaction easier to proceed.

[0104] Application Examples 1-9

[0105] The high entropy alloy nanowires prepared in Examples 1-9 were mixed with commercial carbon powder in a mass ratio of 1:2.4 to obtain a composite catalyst, which corresponds to Application Examples 1-9 respectively.

[0106] Comparative application example 1

[0107] The alloy prepared in Comparative Example 1 was mixed with commercial carbon powder in a mass ratio of 1:2.4 to obtain a composite catalyst.

[0108] Comparative Application Example 2

[0109] No product was generated in Comparative Example 2.

[0110] Comparative Application Example 3

[0111] The alloy prepared in Comparative Example 3 was mixed with commercial carbon powder in a mass ratio of 1:2.4 to obtain a composite catalyst.

[0112] Comparative Application Example 4

[0113] This comparative application example provides a commercial Pt / C catalyst.

[0114] The composite catalysts prepared in Application Examples 1-9 and Comparative Application Examples 1-3 and the commercial Pt / C catalyst provided in Comparative Application Example 4 were subjected to linear sweep voltammetry (LSV) test. The test parameters were as follows: scanning voltage 0.05-1.05 V, scanning rate 5 mV / s, rotation speed 1600 rpm, and under oxygen flow conditions, 0.02 mg of the composite catalyst was dripped onto the glassy carbon electrode tip, with an area of ​​0.196 cm 2 , the initial mass activity value of 0.9V was calculated, and the specific test data are shown in Table 2.

[0115] Table 2

[0116] project 0.9V initial mass activity (mA / mg) Application Example 1 336 Application Example 2 311 Application Example 3 279 Application Example 4 177 Application Example 5 156 Application Example 6 135 Application Example 7 221 Application Example 8 206 Application Example 9 143 Comparative application example 1 133 Comparative Application Example 2 / Comparative Application Example 3 123 Comparative Application Example 4 104

[0117] Note: “ / ” indicates that no product was generated and the activity test could not be performed.

[0118] The test results show that:

[0119] (1) It can be seen from Application Examples 1 to 9 that when the Pt loading in the composite catalyst is relatively high, it is dispersed in the catalyst, providing more active sites for oxygen reduction catalysis, and exhibiting a higher initial mass activity of 0.9 V;

[0120] Furthermore, when the molar ratio of the nucleating agent, the complexing agent, the ammonium salt and the non-precious metal salt is limited to 1:(10-500):(200-1500):(0.5-10), the appropriate atomic ratio of Pt to the non-precious metal adjusts the electronic properties of Pt to a certain extent, that is, the transition metal may act as an electron donor or acceptor, adjust the electron density on the Pt surface, affect the adsorption and reaction of oxygen molecules, and thus optimize the kinetics of the oxygen reduction reaction. At the same time, the addition of an appropriate amount of transition metal may change the atomic arrangement on the platinum surface and provide more active sites.

[0121] (2) It can be seen from the comparative application examples 1 and 3 that when a high entropy alloy with a non-nanowire morphology is prepared, the inconsistent crystal orientation at various locations affects the adsorption and desorption of oxygen intermediates, while reducing the conductivity and hindering the smooth transmission of electrons in the ORR reaction, thereby reducing the activity of the composite catalyst.

[0122] (3) It can be seen from Application Example 1 and Comparative Application Example 4 that in the composite catalyst of Application Example 1 of the present invention, the Pt loading is about 13wt%, and the 0.9V initial mass activity is 336mA / mg, while in Comparative Application Example 4, the Pt loading is 20wt%, which is significantly higher than that of Application Example 1, but the 0.9V initial mass activity is only 104mA / mg. This further shows that the composite catalyst provided by the present invention still has a relatively high activity even if the Pt loading is small, which is more than 3 times higher than that of the commercial Pt / C catalyst.

[0123] In summary, the present invention provides a high entropy alloy nanowire, a preparation method thereof and a composite catalyst. A platinum source, a palladium source and a non-precious metal salt are used as reaction raw materials of the high entropy alloy nanowire, and a magnetic field is added. During the reduction process, the nucleation and growth process of magnetic metal particles and the self-assembly behavior of magnetic nanocrystals are regulated by magnetic force, so that high entropy alloy nanowires with adjustable diameter and length, consistent growth direction, purity, high dispersion, stable structure and uniform Pt dispersion can be prepared at room temperature and normal pressure. The composite catalyst obtained after mixing with commercial carbon powder has rich active sites and excellent oxygen reduction catalytic activity.

[0124] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing high entropy alloy nanowires, characterized in that: The preparation method comprises the following steps: placing the metal precursor mixed solution under an external magnetic field, adding a reducing agent to carry out a reduction reaction, and obtaining high entropy alloy nanowires; Wherein, the metal precursor mixed solution comprises a nucleating agent, a complexing agent, an ammonium salt, a non-precious metal salt and a solvent; The nucleating agent includes a platinum source and a palladium source; The non-noble metal salt includes a combination of at least three of iron salt, cobalt salt, nickel salt, copper salt or manganese salt.

2. The preparation method according to claim 1, characterized in that: Among the non-precious metal salts, the molar ratio of iron salt, cobalt salt, nickel salt, copper salt and manganese salt is 1:(0-10):(0-10):(0-5):(0-5), and the molar amount of at least two metal salts is not zero.

3. The preparation method according to claim 1 or 2, characterized in that: In the metal precursor mixed solution, the molar ratio of the nucleating agent, the complexing agent, the ammonium salt and the non-precious metal salt is 1:(10-500):(200-1500):(0.5-10); Preferably, in the metal precursor mixed solution, the concentration of the metal element is 0 mmol / L-0.5 mmol / L, and is not zero.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The metal precursor mixed solution also includes a pH regulator; Preferably, the pH of the metal precursor mixed solution is 3-14, preferably 8-13.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The field strength of the external magnetic field is 0.0001T-10T.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The reducing agent includes sodium borohydride; Preferably, the molar ratio of the reducing agent to the metal element is (2-100):1; Preferably, the reduction reaction is carried out at room temperature; Preferably, the reduction reaction time is 0.01h-24h.

7. The preparation method according to any one of claims 1 to 6, characterized in that: After the reduction reaction, solid-liquid separation, washing and drying are also included; Preferably, the solid-liquid separation method includes separation using magnets.

8. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: The nucleating agent, the complexing agent, the ammonium salt and the non-precious metal salt are dissolved in a solvent and mixed evenly, a pH adjusting agent is added to obtain a metal precursor mixed solution with a pH of 8-13, the solution is placed under an external magnetic field with a field strength of 0.0001T-10T, a reducing agent is added to carry out a reduction reaction, and after reduction at room temperature for 0.01h-24h, the reaction product is separated by a magnet, and after washing and drying, a high entropy alloy nanowire is obtained; Wherein, the nucleating agent includes a platinum source and a palladium source; the non-precious metal salt includes a combination of at least three of iron salt, cobalt salt, nickel salt, copper salt or manganese salt; in the non-precious metal salt, the molar ratio of iron salt, cobalt salt, nickel salt, copper salt and manganese salt is 1:(0-10):(0-10):(0-5):(0-5), and the molar amount of at least two metal salts is not 0; in the metal precursor mixed solution, the molar ratio of nucleating agent, complexing agent, ammonium salt and non-precious metal salt is 1:(10-500):(200-1500):(0.5-10); in the metal precursor mixed solution, the concentration of metal element is 0mmol / L-0.5mmol / L, and is not 0; the reducing agent includes sodium borohydride; the molar ratio of the reducing agent to the metal element is (2-100):

1.

9. A high entropy alloy nanowire prepared according to the preparation method according to any one of claims 1 to 8, characterized in that: The high entropy alloy nanowire has a diameter of 100nm-300nm and a length of 5μm-80μm.

10. A composite catalyst, characterized in that: The composite catalyst comprises a high entropy alloy nanowire prepared by the preparation method according to any one of claims 1 to 8, or a high entropy alloy nanowire according to claim 9.

Citation Information

Patent Citations

  • Three-dimensional metal nanowire and preparation method thereof

    CN107309439A

  • Metal nanometer wire, dispersion liquid and preparation method of metal nanometer wire and dispersion liquid

    CN107377993A

  • Platinum-based high-entropy alloy nanowire catalyst and preparation method thereof

    CN114196981A

  • Two-dimensional high-entropy alloy nanosheet as well as preparation and application thereof in electrocatalytic oxygen reduction

    CN117340234A

  • Ferromagnetic metal nanowire

    JP2016135920A

Cited By

  • Method for preparing FePt-based high-entropy alloy nanoparticles through high-intensity magnetic field assisted wet chemical method

    CN120115708A

  • High-entropy alloy coated ternary material as well as preparation method and application thereof

    CN120749144A